The Impact of Compulsory Education on Employment and Earnings in a Transition Economy - Jacek Liwiński (Global Labor Organization (GLO), 2018)
In 1966 the minimum school-leaving age was increased from 14 to 15 years in Poland. This was a result of extending the primary school education from 7 to 8 years. At the same time, the reform did not affect the education system at post-primary levels, that is the system of secondary and higher education. In result, all education tracks were extended by one year. Using the regression discontinuity design and data from the Polish LFS (2001-2005), we find that the reform had no impact on men's and women's hourly earnings and employment rate. A similar finding was reported earlier for a few Western European countries. However, our study is the first one to estimate the impact of the compulsory schooling extended in a centrally planned economy on the individuals' labour market outcomes in the period of economic transition. Besides, we find that the reform had a negative impact on the hourly earnings of individuals with primary education.
Keywords: I21; I26; J24; 330; education; schooling; earnings; regression discontinuity design